A reactedness model for local extinction and reignition phenomena in turbulent jet diffusion flames - Koutmos, Panayiotis; Mavridis, Costas (Computer Assisted Methods in Engineering and Science, 1999)
An approach for modeling finite-rate chemistry effects such as local extinction and reignition in piloted diffusion flames of CO/H2/N2 or CH4 and air is presented. A partial equilibrium/two-scalar exponential PDF combustion model is combined with a 2D Large Eddy Simulation procedure employing an anisotropic subgrid eddy-viscosity and two equations for the subgrid scale turbulent kinetic and scalar energies. Statistical independence of the PDF scalars is avoided and the required moments are obtained from an extended scale-similarity assumption. Extinction is accounted for by comparing the local Damkohler numer against a ’critical’ local limit related to the Gibson scalar scale and the reaction zone thickness. The post-extinction regime is modelled via a Lagrangian transport equation for a reactedness progress variable that follows a linear deterministic relaxation to its mean value (IEM). Comparisons between simulations and measurements suggested the ability of the method to calculate adequately the partial extinction and reignition phenomena observed in the experiments.